Online educational populism and New Right 2.0 in Australia and England. (15th March 2022) - Watson, Steven; Barnes, Naomi
ABSTRACT: In this paper, we consider educational populism on social media in England and Australia. In both contexts, academics are positioned as a key constituent of an unjust elite with previously voiceless teachers (UK) and students (Australia) framed as the 'just people'. While populism often speaks to nations and nationalism, as 'the people' against an 'unjust elite' or 'other', micropopulism concerns a particular community against an elite. Although educational micropopulism has been catalysed by social media, there is an underlying political project growing from the New Right coalition of economic liberals and social conservatives. New Right 2.0, a contemporary reformulation of New Right, has an agenda that goes beyond promoting free-market hegemony to promoting civic capitalism and exploits a hybridised media environment to set a policy agenda through provoking polarisation. While there are similarities in New Right 2.0 strategies in England and Australia, the key difference is the way in which micropopulism has emerged and how it plays a role in the hybridised media ecology. We develop a theoretical account of the phenomena of educational micropopulism and offer an understanding of contemporary forms of populism that reflect the sub-national as well as international dimensions of micropopulist.